#TITLE_ALTERNATIVE# - Salman A. N. (NIM 20194007), M.
ABSTRACT: In this paper we consider the following second order nonlinear differential equations . (formula) Oscillation criteria for the above equation will be established by modifying the methods that have been used previously. The results obtained will contain the new oscillation criteria.